2019
DOI: 10.1182/bloodadvances.2018023960
|View full text |Cite
|
Sign up to set email alerts
|

Generation of transgenic zebrafish with 2 populations of RFP- and GFP-labeled thrombocytes: analysis of their lipids

Abstract: Zebrafish thrombocytes are similar to mammalian platelets. Mammals have young platelets (also called reticulated platelets) and mature platelets. Likewise, zebrafish have 2 populations of thrombocytes; one is DiI-C18 (DiI)+ (DP), and the other is DiI− (DN). However, the mechanism of selective thrombocyte labeling by DiI is unknown. Furthermore, there is no transgenic zebrafish line where DP and DN thrombocytes are differentially labeled with fluorescent proteins. In this study, we found that Glo fish, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…We used the GloFli adult zebrafish, where young thrombocytes were labeled with RFP, and mature thrombocytes were labeled with more intense GFP. This adult zebrafish line, GloFli, was previously characterized in our laboratory [ 4 ]. We collected 2 μL of blood from a single fish and subjected this to flow cytometry for separating RFP+ and GFP+ cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used the GloFli adult zebrafish, where young thrombocytes were labeled with RFP, and mature thrombocytes were labeled with more intense GFP. This adult zebrafish line, GloFli, was previously characterized in our laboratory [ 4 ]. We collected 2 μL of blood from a single fish and subjected this to flow cytometry for separating RFP+ and GFP+ cells.…”
Section: Resultsmentioning
confidence: 99%
“…The comparative analysis of the GFP+ and RFP+ thrombocytes showed, more highly expressed genes in GFP+ thrombocytes compared to RFP+ thrombocytes, as confirmed by the heat map studies, probably because during maturation more number of genes are turned on while less number of genes are silenced. In our previous work on young and mature thrombocytes, we have shown that there was an increase in the expression of a Fli1 in mature thrombocytes [ 1 , 4 ]. These results are consistent with the heatmap results suggesting that maturation of thrombocytes involves an increase in thrombocyte gene expression [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations